Electrically Tunable Four-Mirror Gyrotron with Crossed Fields - A. A. Kurayev; V. V. Matveyenka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2023)
In a four-mirror gyrotron, a wide multi-screw electron beam, being in crossed electric and longitudinal magnetic fields, drifts with a velocity vd = E0 /B0 in the direction of the T-wave propagation between the resonator mirrors (co-current wave) or in the opposite direction (counter-propagating wave). In this case, in accordance with the Doppler effect, the generation frequency ω is determined from the synchronism conditions as ω ≈ kωl(1±βd), βd = vd /с. Thus, a change in E0 changes ω, i. e. electrical frequency tuning is carried out. The article presents a diagram of the design of a two-beam four-mirror gyrotron. The calculations were carried out for βd = 0.5, q = β||/β⊥ = 2, the interaction was carried out at the frequency harmonic number k = 1. The tuning band was 20 %. The maximum efficiency is 48 %, the minimum is 33 %. Since the calculations were performed for dimensionless parameters, i.e., having a universal character, the physical characteristics of the gyrotron at a wavelength λ = 6 mm (f0 = 50 GHz) and a loaded resonator quality factor Ql = 200 were as follows: electron beam current I0 = 60 A, B0 = 2 T, voltage U0 = 79 kV, efficiency = 48 %.